2012
DOI: 10.3892/ijo.2012.1433
|View full text |Cite
|
Sign up to set email alerts
|

Expression of multidrug resistance-associated proteins in paediatric soft tissue sarcomas before and after chemotherapy

Abstract: Abstract. Expression of multidrug resistance (MDR) proteins is thought to significantly contribute to the different biological/ clinical behaviour of soft tissue sarcomas (STS) of various histological types and clinicopathological stages, as they are responsible for active efflux of cytotoxic drugs from tumour cells. We investigated the expression of 3 MDR proteins, i.e., permeability glycoprotein 1 (P-gp), multidrug resistance-associated protein 1 (MRP1) and multidrug resistance 3 (MDR3), in 43 STS specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For MRP1 , high levels of the gene were associated with poor prognosis and high histological grade in childhood neuroblastoma [40–42], soft tissue sarcoma [43], and non-small cell lung cancer [4446], and with recurrence in breast cancer patients who were treated with chemotherapy [47]. To our knowledge, only one previously reported study suggested the existence of a common expressing regulatory mechanism between MDR3 and MRP1 in high-risk tumours such as breast cancers and nephroblastoma [48]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For MRP1 , high levels of the gene were associated with poor prognosis and high histological grade in childhood neuroblastoma [40–42], soft tissue sarcoma [43], and non-small cell lung cancer [4446], and with recurrence in breast cancer patients who were treated with chemotherapy [47]. To our knowledge, only one previously reported study suggested the existence of a common expressing regulatory mechanism between MDR3 and MRP1 in high-risk tumours such as breast cancers and nephroblastoma [48]. …”
Section: Discussionmentioning
confidence: 99%
“…Resistance to chemotherapy may be due to high expression of multidrug resistance mechanisms already present in tumor cells before treatment, and/or it is also possible that chemotherapy modulates the expression of multidrug resistance proteins reducing treatment efficacy. Several studies showing that expression of MRP1 and MDR3, among others multidrug resistance genes may induce or increase after chemotherapy in pediatric tumors, soft tissue sarcomas and malignant melanoma [33, 48, 55]. In the SIOP-93-01 protocol, vincristine and actinomycin D treatment were given to the patient with localized tumor, and doxorubicin was included in patients with metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…In some types of cell lines, e.g., doxorubicin-resistant LoVo cells, ABCB4 expression was increased to a higher degree than ABCB1 expression, which suggesting that the predominant transporter that was responsible for doxorubicin resistance may be ABCB4 [16]. A marked increase of ABCB4 expression was also found in surgical specimens from patients with soft-tissue sarcomas and Wilms tumour after chemotherapy [17,18]. However, the exact role of ABCB4 in doxorubicin resistance is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that ABCB4 can also act as an efflux transporter to limiting the intracellular accumulation of drugs such as digoxin, paclitaxel, daunorubicin, vinblastine, and ivermectin [13]. Recently, accumulating evidence indicates that ABCB4 is overexpressed in cancer cells after exposure to some chemotherapeutic drugs including doxorubicin [14][15][16][17][18], which implicate the involvement of ABCB4 in the acquired resistance to these anticancer agents. However, the exact role of ABCB4 in doxorubicin resistance as well as the potential mechanisms still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Clonal selection of MDR protein-expressing tumour cells and up-regulation of MDR proteins were thought to be the possible explanations for increased expression of MDR proteins in post-treatment specimens. 45 Serum and glucocorticoid inducible kinase expression in RMS has been shown to be associated with treatment resistance in RMS cell lines. 46 In vitro and in vivo studies in RMS have shown that GST mediates chemotherapy resistance.…”
Section: Pathophysiology Of Treatment Refractorinessmentioning
confidence: 99%